Web-Based Media through Project Based Learning Approach to Support OBE Learning - Yudhistira Anggraini; Erni Erni; Ulfa Annida Damanik; Dermawan Pakpahan; Rahmi Rahmi; Qothrun Nada Ma’ruf Batubara (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
Outcome-Based Education (OBE) is an educational system oriented toward achieving measurable learning outcomes as the basis for planning, implementing, and evaluating learning. Implementing OBE in higher education requires learning innovations that can optimally support the achievement of graduate competencies. This research aims to develop web-based learning media through a Project-Based Learning (PjBL) approach and to test its feasibility and effectiveness in the Children's Fashion course. This study used a Research and Development (R&D) method with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. During the needs analysis phase, 92.5% of lecturers and 89.27% ??of students expressed a very high need for the development of web-based learning media. Product validation results showed that the assessment by material experts was 88.6% and the media experts 89%, both of which are in the very good category. User trials also showed positive results, with 81% of the small group, 85% of the medium group, and 87% of the large group, all in the good to excellent category. The effectiveness analysis showed that the average pretest score of 44.29 increased to 78.27 in the posttest. Furthermore, the N-Gain calculation was 0.61, which is in the moderate category. Based on these results, it can be concluded that the web-based learning media developed using the Project-Based Learning approach is feasible and quite effective in improving student learning outcomes in the Children's Fashion course and supporting the implementation of an OBE-based education system